Asuhan Keperawatan Pada An. B Dengan Gangguan Sistem Pernapasan : Pneumonia Di Ruang Anggrek RSUD Surakarta - Wahyuningsih, Endang; , Siti Arifah, S.Kp., M.Kes (2015)
NURSING CARE On CHILD. B WITH RESPIRATORY SYSTEM DISORDERS OF PNEUMONIA ON ANGGREK ROOM HOSPITAL SURAKARTA (Endang Wahyuningsih, 2015, 68 pages) ABSTRACT Background : Pneumonia is a disease due to an infection that can cause death at the age of five. Every year, pneumonia kills about 1.6 million children under five. (WHO, 2009). The percentage of pneumonia in Indonesia in 2008 increased to 49.45%. Year 2009 was 49.23% and in 2010 dropped by nearly 39.38% of the number of children under five in Indonesia (Depkes RI, 2012). In Central Java, the coverage of cases of pneumonia each year toddler fell from the national target. In 2009 the discovery of cases of pneumonia be 25.69% and the discovery of cases of pneumonia national targets by 86%. (Dinkes Jateng, 2009) Objective: To know the nursing care Pneumonia with the Clients include assessment, intervention, implementation, and evaluation of nursing. Results: The taxable income do nursing care 3 x 24 hours findings obtained, ineffective airway clearance resolved partially, breathing pattern effective not resolved partially, partially resolved risk development disorders. Conclusion: Cooperation between the health care team Clients with or Family Indispensable for success nursing care, therapeutic communication can encourages Client And Family more Cooperative, nebulizer therapy can reduce shortness of breath so that the airway back effectively, train exhibit rather client and baby massage can reduce risk the development disorders. Keywords: Pneumonia, ineffective airway clearance, Pattern way not effectively, risk development disorders.